The Cambodian Incursion: American War of Ideology, 1969-1970 - TOUFOUTI, Youcef (Journal of Human Sciences, 2014)
This article is dedicated to the Cambodian incursion and it mainly focuses on U.S. foreign policy toward Cambodia between 1969 and 1970. This small neutral country marked the continuation of the conflict between the American and the Soviet ideologies that would vie for global influence throughout most of the twentieth century. The idealistic aspect of the conflict was the basic premise that being allied to America was good for humanity. Americans were supposedly protecting democracy or the possibility of democracy against a Stalinist dictatorship. Ironically, the Vietnamese were allied to the Soviet Union and their firmest hopes of future were placed on the prospect of a union between the North and the South. The idea, after all, turned neutral Cambodia into a major player in the strategic game- a state squeezed between imperial powers.